The association between umbilical cord blood fat-soluble vitamin concentrations and infant birth weight - Yang, Guicun; wang, Nianrong; Liu, Hao; Si, Lina; Zhao, Yan (Frontiers in Endocrinology, 2023)
Background: Fat-soluble vitamins, including vitamins A, D and E, play an important role in the regulation of glucose and lipid metabolism, and may affect infant birth weight. Evidence on the association of birthweight with fat-soluble vitamins is controversial. Therefore, this study aims is to determine the associations of birthweight with vitamin A, D，and E concentrations in cord blood. Methods: A total of 199 mother–infant pairs were enrolled in the study. According to gestational age and birth weight, the mother–infant pairs were divided into small for gestational age (SGA), appropriate for gestational age (AGA), and large for gestational age (LGA). The Vitamin A, D，and E concentrations in serum were measured by high-performance liquid chromatography tandem-mass spectrometry. Results: The concentrations of vitamin A in the SGA group were significantly lower than those in the AGA and LGA groups. The concentrations of vitamin E in the SGA group were significantly higher than those in the AGA and LGA groups. However, no significant differences were observed in vitamin D among the three groups. Being male (β = 0.317, p < 0.001) and birth weight (β = 0.229, p = 0.014) were positively correlated with the levels of vitamin A. Birth weight (β = -0.213, p= 0.026) was correlated with lower levels of vitamin E. No correlation was found between influencing Factors and the levels of vitamin D (p> 0.05). After adjusting for gestational age, sex, mother’s age, delivery mode, pre-pregnancy BMI, and weight gain during pregnancy, the levels of cord blood vitamin A were positively correlated with birth weight (p=0.012). Conclusions: The infant’s birth weight is associated with the levels of cord blood vitamins A and E. The dysregulation of vitamins A and E in infants may be a risk factor for fetal growth and future metabolic diseases.